الألعاب اللغوية الحسية ودورها في تعلم اللغة العربية السنة الأولى ابتدائي أنموذجا - دراسة ميدانية - زهواني, رشيدة; سليمة, جيلاخ (جامعة الوادي - University of Eloued, 2023)
يعتبر أسلوب التعلم باستخدام الألعاب التربوية عامة، والألعاب اللغوية الحسية خاصة، من أساليب التعلم النشط، وهو أسلوب تربوي هادف، مشوق وممتع لجميع المستويات التعليمية وبالأخص المرحلة الابتدائية، وتحديدا السنة الأولى كونها أول سنة للتعلم الإلازمي، ولكل المواد الدارسية بما فيها اللغة العربية، باعتبارها اللغة الوطنية الرسمية. لذا وجب على المتعلم أن يتمكن من مهاارتها، بل ويتقنها، ولا يتحقق ذلك إلا باكتساب أسس القارءة، التي هي مفتاح المعرفة، ولأن متعلم السنة الأولى طفل، فإن اللعب هو أيسر الطرق وأفضل الوسائل في اكتسابه المعرفة وتقريب مبادئ العلم. فالألعاب اللغوية الحسية تؤدي دوار فعالا في جعل المتعلمين أكثر نشاطا وتفاعلا واستيعابا، ومن هذا المنطلق ركزت دارستنا على بعض الجوانب التي مكنت المتعلم من اكتساب اللغة العربية وتنمية مهاارته، فكانت موسومة بـ" :الألعاب اللغوية الحسية ودورها في تعلم اللغة العربية -السنة الأولى ابتدائي أنموذجا-." [2] Abstract: Using educational games, particularly sensory language games, is considered an active, learning engaging method. It is an international, engaging, and enjoyable educational approach for all educational levels with a special emphasis on the elementary school stage, specifically the first year, as it marks the beginning of compulsory education. This approach applies to all subjects, including the Arabic language, which the official national language. Therefore, learners need to acquire and master it is skills, especially the foundations of reading, which is the key to knowledge. Since first year learners are children, play becomes the easiest and best way for them to acquire knowledge and introduce the principles of science. Sensory language games play an effective role in making learners more active, interactive, and receptive. Based on this perspective, our study focused on certain aspects that enabled learners to acquire the Arabic language and develop their skills. It was titles: sensory language games and their role in learning the Arabic language first year of elementary schools as a model.
لسانيات عامة
Keywords: الألعاب اللغوية الحسية، تعلم اللغة العربية، السنة الأولى ابتدائي; Sensory language games, learning the Arabic language, the first year of primary school